The reproductive value in distributed optimal control models - Stefan Wrzaczek; Michael Kuhn; Alexia Prskawetz; Gustav Feichtinger (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2009)
We show that in a large class of distributed optimal control models (DOCM), where population is described by a McKendrick type equation with an endogenous number of newborns, the reproductive value of Fisher shows up as part of the shadow price of the population. Depending on the objective function, the reproductive value may be negative. Moreover, we show results of the reproductive value for changing vital rates. To motivate and demonstrate the general framework, we provide examples in health economics, epidemiology, and population biology.
Keywords: 300; Reproductive value; distributed optimal control theory; McKendrick; shadow price; indirect effect; health economics; epidemiology; population biology; Bevölkerungsentwicklung; Opportunitätskosten; Kontrolltheorie; Gesundheitsökonomik; Theorie